FACTUAL AND LEGAL INTEREST IN THE CONTRACT OF PROPERTY INSURANCE - N. Petrov (Гуманитарные и юридические исследования)
The article is devoted to one of the most meaningful and therefore controversial concepts, such as title insurance. The author considers the legal nature of an insurable interest in the title insurance and the legal consequences of its absence.